Review of Recent Development on Preparation, Properties, and Applications of Cellulose-Based Functional Materials - Ya-Yu Li; Bin Wang; Ming-Guo Ma; Bo Wang (International Journal of Polymer Science)
Cellulose is the most abundant biomass resource in the world. It can be transferred to various water soluble derivatives, biochemicals, and materials. In the second half of the 20th century, nanocellulose was extracted with unique properties such as optical transparency, high strength, and high surface area. These new forms of cellulose can be combined with other materials, mainly biopolymers, to form multifarious composites, which are used in all applications of human life. For convenience, to introduce the recent development of these cellulose-based functional composites, we divided them to seven categories, including biological applications, water treatment, sensor, reinforcing agent, energy storage materials, Pickering emulsion stabilizer, and other versatile applications. The preparation, properties, and applications of these functional composites were depicted.